Salivary changes in oral mucosal diseases. Issue 1 (February 2016) - Hassona, Yazan; Scully, Crispian
Abstract: Saliva is a unique biological fluid that can be easily collected and analyzed with low cost and low morbidity. Therefore, there is a growing attention for using salivary biomarkers in the diagnosis and monitoring of disease progress and response to treatment. Salivary changes have been described in relation to oral mucosal diseases. This article discusses the causes and consequences of salivary hypofunction and presents a review of the literature related to changes in salivary parameters in various oral mucosal diseases and in systemic diseases with possible oral mucosal involvement.